2013
DOI: 10.1007/s10072-013-1291-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma copeptin levels in Chinese patients with acute ischemic stroke: a preliminary study

Abstract: Copeptin is a stable by-product of arginine-vasopressin synthesis and reflects its secretion. The objective of the study was to evaluate the predictive value of copeptine on functional outcome at 90-day follow-up from stroke onset. We conducted a prospective, observational cohort study in the emergency department of two hospitals and enrolled 125 patients with acute ischemic stroke. Plasma copeptin concentrations, determined by a CT-proAVP-luminescence-immunoassay, were measured. There was a good correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
5
22
0
Order By: Relevance
“…Another study was identified in the hand-searching. From the selected articles, three studies recruited patients with intracerebral hemorrhage [87,92,93], one with subarachnoid hemorrhage [88] and the other seven articles included ischemic stroke patients [85,86,89,[94][95][96][97].…”
Section: Hormones Of the Hpa Axismentioning
confidence: 99%
“…Another study was identified in the hand-searching. From the selected articles, three studies recruited patients with intracerebral hemorrhage [87,92,93], one with subarachnoid hemorrhage [88] and the other seven articles included ischemic stroke patients [85,86,89,[94][95][96][97].…”
Section: Hormones Of the Hpa Axismentioning
confidence: 99%
“…29 Potentially supporting this association in ICH, previous studies on the neurohormone copeptin, the C-terminal portion of provasopressin, which is cosecreted with AVP from the hypothalamus, 30 report that increased copeptin was a marker of poorer outcome, which was shown in subarachnoid hemorrhage, ischemic stroke, and also in patients with ICH. [31][32][33] Despite these hypothetical pathophysiological considerations of hyponatremia-mediated effects on outcome, it remains unresolved whether hyponatremia simply represents a bystander of disease, that is, preexisting comorbidity or polymedication reflecting poorer overall status, which itself may be responsible for worse outcome. This aspect is even more important in light of the findings presented here, because all hyponatremia patients presented with hyponatremia on hospital admission rather than developed it during clinical course.…”
Section: May 2014mentioning
confidence: 99%
“…Four studies measured the outcome at three months, but could not confirm a link with the prognosis in their own analyses [21][22][23][24]. In the studies that did reach significance, two measured the outcome at three months, one at discharge and one at 48 h [16,18,24,25].…”
Section: Discussionmentioning
confidence: 93%